Commercial preslaughter blue light ambience for controlling broiler stress and meat qualities - Barbosa,Claudia Freitas (2013)
The objective of this work was to study the effect of blue light diffuser on the broiler stress control by measuring the occurrence of PSE meat just before slaughtering. Birds were divided into the following two groups before slaughter at the point of being hung on shackles: broiler group under low intensity blue light ambience (475, 17-20 lx) and control group under white light (550-650nm, 321-332 lx). Birds' stressful conditions were measured by the occurrence of PSE meat. Breast fillets were classified as PSE meat based on pH (<5.8) and lightness (L*> 53.0). The fillet samples in the control group had the following characteristics: pHu=5.77, L* = 54.26 and b*= 6.27. The fillet samples from birds under blue light ambience had the following characteristics: pHu=5.81, L* = 52.86 and b* = 5.22 (p < 0.05). These results revealed that the treatment of blue light ambience just before slaughtering contributed to the alleviation of ante mortem stress of the birds, which was observed by a 14% decrease in the occurrence of PSE meat. Exposure to blue light just before slaughtering was shown to have potential to be used in modern slaughterhouses to offer a comfortable atmosphere, thereby maintaining breast meat quality.